An exploratory study on time perspective as a possible indicator of audiological help-seeking behaviours and intervention outcomes, in Gauteng South Africa - Araujo, Monica L. (My University, 2023)
Time perspective is a basic psychological construct that is vital in indicating several health-related behaviours. Whilst numerous indicators of audiological help-seeking behaviours and intervention outcomes such as age, perceived severity of hearing loss, gender, and stigma, have been studied, there is a large paucity of research on time perspective within the audiological field. Therefore, time perspective, which is frequently depicted as one of the most powerful influencers on human behaviour, has guided this study by researching whether it may indeed indicate audiological help-seeking behaviours and intervention outcomes. The study set out to explore patient perceptions of the theme of time and the possible impact of time perspective on audiological help seeking behaviours and intervention outcomes. The researcher also explored audiological experiences that may relate to different aspects of time perspective. Finally, participants were asked to provide advice on how audiologists could consider the aspect of time and time perspective within the audiological journey of patients. To address the research aims and objectives, a cross-sectional, qualitative, exploratory research design using inductive and narrative approaches, was implemented at a private practice in the South of Johannesburg. The participants included adults who are hearing aid users and attend the private practice for audiological services. These participants were recruited through purposive, convenience, and maximum variation sampling. Data were obtained through conducting semi-structured interviews and two focus groups. The data was then analysed using the Framework Method. Several important themes and sub-themes emerged, which mainly indicated the perception that different time perspectives, namely, future orientated, present-hedonistic, present-fatalistic, past-negative, or past-positive, influence the audiological help-seeking behaviours and intervention outcomes of individuals in different ways. Due to this, and the perceived important influence of time perspective on audiological behaviours, participants advised the use of a time perspective tool as well as distinct approaches to be used by audiologists, based on the different time perspectives of patients, to ensure the best audiological journey for all. Findings therefore suggested that time perspective may indeed indicate audiological help-seeking behaviours and intervention outcomes. As this study was exploratory in nature, it would be beneficial to study it on a larger scale using quantitative methods. In the interim, it was advised that time perspective should be a psychological construct with which audiologists ought to familiarise themselves.
A dissertation submitted in partial fulfilment of the requirements for the degree of Master of Arts in Audiology to the Faculty of Humanities, University of the Witwatersrand, 2023
Keywords: Time perspective; Audiological helpseeking behaviours; Hearing loss